Experimental and numerical research on the underwater sound radiation of floating structures with covering layers. (February 2015) - Zhu, Dawei; Huang, Xiuchang; wang, Yu; Xiao, Feng; Hua, Hongxing
This paper presents experimental and numerical investigation into the underwater sound radiation characteristics of a free-floating stiffened metal box covered with three different kinds of covering layers and subjected to mechanical excitation. One box is bare while the other three are, respectively, covered with solid covering layers, chiral covering layers, and chiral covering layers filled with expanded polystyrene (EPS) foams. The equivalent elastic modulus of chiral covering layer is obtained by the homogenization theory. The finite element method and boundary element method are used to calculate the underwater sound pressure. The measured and numerical results are illustrated and the sound insulation mechanisms of three covering layers are discussed. The measured results agree with the numerical results well. The covering layers can obviously reduce the underwater sound radiation of floating structures. Compared with the solid covering layer, the chiral covering layer is less effective in suppressing the sound radiation in the low-frequency range but more effective in the medium- and high-frequency range. The chiral covering layer filled with EPS foams shows the best performance, which is more effective in suppressing the sound radiation both in the low-frequency range and in the medium-frequency range. The EPS foams have a high contribution to the added damping of the chiral covering layer.